Performance-based and authentic assessment for Cambridge PRE A1 Starters exam (Živi jezici: Journal for Foreign Languages and Literatures, 2022)
The aim of this paper is to present possibilities of transforming activities from English courses for Young Learners into activities which will help them become aware of the elements that comprise Pre A1 Starters, formerly known as Cambridge YLE Starters Exam. The proposed activities focus on two important aspects of an exam: the ways to minimize student-related unreliability and the ways to maximize test validity, to bring test format closer to students. It also considers important aspect of learning – background knowledge, since new knowledge is most effectively acquired by building on existing one. This has led to using alternative assessment as the most suitable way to implement prior knowledge, as well as make young students reflect on their own learning. The paper presents ways of self-assessment and peer assessment of authentic and performance-based activities as they best fit the student’s book and portfolio tasks prescribed by the course book used.
Keywords: self-assessment; peer assessment; reading; writing; speaking; alternative assessment; scoring rubrics